2009
DOI: 10.1097/bsd.0b013e3181778181
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Myelopathy Accompanied With Hypoplasia of the Posterior Arch of the Atlas

Abstract: In the presence of congenital hypoplasia of the posterior arch of the atlas, the spinal cord is highly susceptible to injury because congenital spinal canal stenosis is present. Therefore, the presence of even a mild mechanical compressive lesion leads to myelopathy. Acquired mild atlantoaxial subluxation was associated with this hypoplasia, and the association was considered to be the mechanism underlying the occurrence of myelopathy in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Musha and Mizutani 11) who used lateral roentgenograms for the identification of atlas hypoplasia in the Japanese population reported that the average sagittal inside diameter, equivalent to our IAP, was 34.4 mm in women and 37.1 mm in men. They defined hypoplasia as a value with 2 standard deviations (SD) below the standard.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Musha and Mizutani 11) who used lateral roentgenograms for the identification of atlas hypoplasia in the Japanese population reported that the average sagittal inside diameter, equivalent to our IAP, was 34.4 mm in women and 37.1 mm in men. They defined hypoplasia as a value with 2 standard deviations (SD) below the standard.…”
Section: Discussionmentioning
confidence: 81%
“…Their findings suggest the IAP as the optimal parameter for defining atlas hypoplasia. 11,24) As IAP is strongly correlated with CSA (Tables 3 and 4) and IAP is easier to measure than CSA, we suggest that determining the IAP is appropriate for the assessment of atlas hypoplasia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…616,18,2023 Musha and Mizutani measured the sagittal inside diameter (equivalent to our C1 anterior-posterior diameter) of 300 adult Japanese men and women. 18 They also defined hypoplasia as the lowest 2.5% of values. In women, 29.4mm was considered hypoplastic, while 30.5mm was hypoplastic in men.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies examining anatomy at the level of the atlas and axis. 17,18 These studies, however, have been underpowered, performed on radiographs, or both. No adequately powered study exists to define hypoplasia of the atlas.…”
Section: Introductionmentioning
confidence: 99%